Evaluation of mechanical and antimicrobial properties for indigenously developed Biofilm for food packaging industries. Issue 1 (February 2021) - Rengaraju, Balakrishnaraja; Jeevanantham, M; Shanmugaraja, S; Selvakumar, A; Tamilselvi, S
Abstract: The preparation of the film based on aloe vera gel and polyvinyl alcohol (PVA) were carried out in this work. The film has high adhesion due to the presence of polyvinyl alcohol. The mechanical properties like tensile strength and the transparency of the film were tested. The temperature withstanding ability of the film is tested with Thermo gravimetric analysis. The functional groups of the film were identified. The films prepared were evaluated by incorporation of an antifungal and an antibacterial agent which shows marked inhibition on growth of mold, yeast and bacteria. The Shelf life of the vegetables was tested using the film.